2011
DOI: 10.1371/journal.pone.0029093
|View full text |Cite
|
Sign up to set email alerts
|

Expression of B-RAF V600E in Type II Pneumocytes Causes Abnormalities in Alveolar Formation, Airspace Enlargement and Tumor Formation in Mice

Abstract: Growth factor induced signaling cascades are key regulatory elements in tissue development, maintenance and regeneration. Perturbations of these cascades have severe consequences, leading to developmental disorders and neoplastic diseases. As a major function in signal transduction, activating mutations in RAF family kinases are the cause of human tumorigenesis, where B-RAF V600E has been identified as the prevalent mutant. In order to address the oncogenic function of B-RAF V600E, we have generated transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Activated AT‐II cells by inflammatory cytokines can upregulate the surface marker MHC‐II or COX‐2, inducing the differentiation of regulatory T cells (Tregs) (Ragazzo et al, ; Lo et al, ; Gereke et al, ). Thus, understanding the phenotypic alterations of AT‐II cells in response to AFG 1 ‐induced inflammation is especially important considering that activated AT‐II cells are involved in lung carcinogenesis in several animal models (Li et al, ; Zanucco et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated AT‐II cells by inflammatory cytokines can upregulate the surface marker MHC‐II or COX‐2, inducing the differentiation of regulatory T cells (Tregs) (Ragazzo et al, ; Lo et al, ; Gereke et al, ). Thus, understanding the phenotypic alterations of AT‐II cells in response to AFG 1 ‐induced inflammation is especially important considering that activated AT‐II cells are involved in lung carcinogenesis in several animal models (Li et al, ; Zanucco et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that AFG 1 induces ultrastructural and functional impairment in rat AT‐II cells in vitro and vivo (Shen et al, ). Activated AT‐II cells have been shown to be involved in lung carcinogenesis in several animal models (Li et al, ; Zanucco et al, ). Those findings further confirm that AT‐II cells serve as a potential progenitor cells and may play a critical role in Aflatoxin‐induced lung tumorigenesis (Massey et al, ; Guindon et al, ).…”
mentioning
confidence: 99%
“…The RAS-pathway also induces small mother against decapentaplegic-3 (SMAD3) [24,25] and STAT3 [26,27], two transcriptions factors whose phosphorylated versions (pSMAD3, pSTAT3) activate p21 CIP1 gene [28][29][30][31]. Unexpectedly, we found no changes in the percentage of pSMAD3-positive cells among adenomas and non-tumor alveolar areas from both BRAF V600E mice and controls (Supplementary Fig.…”
Section: Effects Of Braf V600e Expression In Lung Adenomasmentioning
confidence: 97%